An overview of key emerging technologies transforming public transportation in the Fourth Industrial Revolution era. Issue 1 (April 2021) - Mbowa, K.; Aigbavboa, C.; Akinshipe, O.; Thwala, D. W.
Abstract: Public transportation connects a large proportion of the world's population to their destination. Hence it is vital to continuously monitor and improve the quality of services offered in line with technological advances in order to enhance travellers' experience. This study aims to assess the technologies within the fourth industrial revolution that can be used to improve travellers' experience of public transportation systems. The study followed a systematic review and extant literature was carefully reviewed to properly understand how new-age technologies can be used to improve travel experience in the public transportation sector. The study revealed that there are five key emerging technologies that can be used to transform the public transportation system. These technologies include operations management systems, traveller information systems, e-fare collection systems, intelligent vehicle and e-security systems. In conclusion, incorporating these emerging technologies with the existing public transportation system will drastically increase operational efficiency and improve travelling experience for users.